Project quality, regulation quality - Elena Mussinelli (Techne)
In the Italian context, the first law directly affecting the urban planning and building sector dates back to approximately 160 years ago, precisely Law 2248/1865. It established the administrative unification of the Kingdom of Italy, empowering municipal councils to deliberate on ‘hygiene, building and local police regulations’, and was followed a few months later by Law 2359/1865 on expropriations for public purpose. By contrast, the first regulations for the protection of artistic, historical, archaeological and ethnographic heritage (1089/1938), and natural beauty (1497/1939), are just over 80 years old. From that time onwards, the rules governing planning and design actions have been considerably enriched and developed. Hence, it is worth reflecting on the effectiveness and efficiency of a regulatory framework that has been governing territorial, urban and building transformations in an increasingly articulated and specialised manner with a view to improving the quality and sustainability of natural and anthropic habitats. Moreover, its ability to govern the ways, times and cultural and technical contents of the project production process to carry out high quality creations is worthy of consideration.